2021
DOI: 10.3390/f12060749
|View full text |Cite
|
Sign up to set email alerts
|

Integrated SMRT Technology with UMI RNA-Seq Reveals the Hub Genes in Stamen Petalody in Camellia oleifera

Abstract: Male sterility caused by stamen petalody is a key factor for a low fruit set rate and a low yield of Camellia oleifera but can serve as a useful genetic tool because it eliminates the need for artificial emasculation. However, its molecular regulation mechanism still remains unclear. In this study, transcriptome was sequenced and analyzed on two types of bud materials, stamen petalody mutants and normal materials, at six stages of stamen development based on integrated single-molecule real-time (SMRT) technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, the stamen petalody was a surprising phenomenon during our investigation ( Figure 3B ). The stamen of the male sterile mutant shows remarkable petalody, increasing whorls of petals and generating different flower forms, which are extremely important traits for ornamental value and serve as a useful genetic tool because they eliminates the need for artificial emasculation ( Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the stamen petalody was a surprising phenomenon during our investigation ( Figure 3B ). The stamen of the male sterile mutant shows remarkable petalody, increasing whorls of petals and generating different flower forms, which are extremely important traits for ornamental value and serve as a useful genetic tool because they eliminates the need for artificial emasculation ( Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput RNA sequencing (RNA-Seq) can generate information-rich sequence and expression data sets to characterize the abundance of related genes in plants [18,19]. RNA-Seq using a unique molecular identifier (UMI) strategy can eliminate quantitative interference by polymerase chain reaction (PCR) amplification preferences, leading to more accurate expression results [20,21]. Hub genes associated with a certain trait can be identified using the weighted gene co-expression network analysis (WGCNA) of RNA-Seq genes based on the UMI strategy associated with trait phenotypic data [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, [6] analyzes Camellia oleifera, which is used for oil production; [7] Liriodendron sino-americanum, a relevant ornamental and afforestation species; and [3] Handeliodendron bodinieri, a rare and endangered species, which is also important for bio-energy, landscaping, and water and soil conservation. The of [4] focuses on Picea likiangensis, one of the dominant tree species in the subalpine forest southwest China, with an important ecological in soil and water and carbon storage; [8] reports findings on Pinus massoniana, a relevant timber well as loblolly and slash pines studied in [9].…”
mentioning
confidence: 99%
“…Reproductive biology, sensu lato, Issue, with a total of five papers. In [6], transcriptome sequencing was used to study the male sterility caused by stamen petalody in Camellia oleifera, whose molecular regulation mechanism remains unclear. The results showed that four MADS transcription factor genes are predicted to be involved to different extents.…”
mentioning
confidence: 99%